The welfare evaluation of primary goods: A suggestion - Antonio Villar (Institute for Advanced Studies (IHS), 2001)
This paper presents a characterization of a welfare index for the evaluation of primary goods (to be understood as those goods that all agents should enjoy equally). The welfare associated with a given distribution of n primary goods among m agents is measured as the sum of n real-valued functions, one for each good, which are increasing in the aggregate consumption and decreasing in its dispersion (measured by Theil's first inequality index). welfare evaluation ; inequality ; primary goods
Keywords: D30; D63; 330; Lebensqualität; Wohlfahrtsanalyse; Soziale Wohlfahrtsfunktion; Rawls-Gerechtigkeitstheorie; Theorie